VIRTUAL REALITY’S ROLE IN INCREASING EMPATHY LEVELS IN MEDICAL STUDENTS: A SYSTEMATIC REVIEW OF QUANTITATIVE STUDIES - Dimas Ardi Bramundito; Diana Listy Nababan; Arif Rachman; Sofiana, Sofiana (Journal of Innovation Research and Knowledge, 2026)
Empathy is a cornerstone of effective medical practice, yet numerous studies indicate a decline in empathy as students advance through medical training. Virtual Reality (VR) offers immersive, experiential learning that can potentially counteract this decline by fostering perspective-taking and emotional engagement. This systematic review analyzed quantitative studies published between 2015 and 2025 assessing VR interventions designed to enhance empathy among medical students. Following PRISMA 2020 guidelines, nine eligible studies (N = 553) were identified from four databases. The included designs comprised five randomized controlled trials (RCTs) and four single-group pre–post studies, primarily utilizing immersive head-mounted VR simulations. Across studies, all reported post-intervention empathy increases, with six demonstrating statistically significant improvements (p < 0.05). The strongest effects were noted in VR simulations portraying stigmatized or vulnerable patient perspectives, such as psychosis, depression, and chronic illness. Methodological appraisal using the MERSQI tool indicated moderate study quality (scores 10–13.5/18). Overall, immersive VR demonstrates measurable effectiveness in improving empathy among medical students, surpassing traditional didactic approaches. However, further large-scale, longitudinal research is required to confirm sustainability and translate self-reported gains into clinical behavioral outcomes.